Investigation of the fermentation filtrate from soapberry (Sapindus mukorossi Gaertn.) pericarp on improving the microbial diversity and composition of the human scalp - Xu, Chong; Pan, Danyang; Zhang, Dexiang; Lin, Lin; Chen, Yiti; Liang, Shuangcheng; He, Jingyu (Frontiers in Microbiology, 2024)
Microorganisms as a component of scalp ecosystem play a vital role in human scalp health. To investigate the effect of the fermentation filtrate of soapberry pericarp on the diversity of scalp microorganisms, 16S and ITS sequences of 198 samples from three different used stages (Day 0, Day 7, Day 28) were sequenced using the Illumina Novaseq platform. The alpha-diversity and beta-diversity analyses showed that scalp microbial diversity and composition were influenced by the fermentation filtrate of soapberry pericarp. Based on functional analysis, this study found an enrichment of healthy scalp-related bacterial pathways, such as amino acid, nucleoside, and nucleotide biosynthesis, while a decrease in fungal pathogenesis pathways, specifically saprotroph and symbiotroph pathways, was observed. In conclusion, the study described about the complex community dynamics of human scalp microorganisms during the stages of using the fermentation filtrate of soapberry pericarp. This result will help rationally utilize the fermentation filtrate of soapberry pericarp to keep or improve human scalp health.